Association of Age and Parity with Pregnancy-Induced Hypertension - Ashraf, Abida; Hameed, Samina; ., Yasmin; Ahmad, Mansoor; Saleem, Muhammad Zeeshan; Ahmed, Ijaz (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association of age and parity with gestational hypertension. Study Design: Case-control study. Place and Duration of Study: Department of Gynaecology and Obstetrics, Combined Military Hospital, Sibi Pakistan, from Oct 2020 to Sep 2021. Methodology: A total of two hundred and sixty-eight (n=268) patients (134 controls and 134 cases) were included in this study. Data about age, parity, economic status and education status was recorded. Two consecutive readings of blood pressure were recorded in sitting position, 4 hours apart, and the second reading was entered on the proforma. Results: Mean age of the patients was 28.10±5.61 years and 28.99±6.29 years in cases and controls, respectively. Mean gestational age was 38.46±1.02 weeks in cases and 38.04±1.00 weeks in controls. In cases, primigravida were 88(65.7%) and multigravida were 46(34.3%) and in controls 58(43.3%) were primigravida and 46(56.7%) were multigravida. Odds ratio was 2.50(95% CI: 1.53-4.10), p value was <0.001. In cases, 111 women (82.8%) were from young age group and 23 women (17.2%) belonged to advanced age group. In controls 94 women (70.2%) were of young age group while 40 women (29.8%) belonged to advanced age group (p value was 0.013). Conclusion: Primigravidae and women of younger age seem to have association with pregnancy induced hypertension